DEVELOPMENT OF FLIPBOOK LEARNING MEDIA IN THE PANCASILA EDUCATION SUBJECT FOR GRADE IV AT SD NEGERI 040544 DOLAT RAYAT - Sinaga, Rian Julfian; Tindaon, Juwita; Ginting, Nurlia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the limited use of interactive learning media in Pancasila Education, especially on the topic of village and sub-district government systems, which made students less active and hindered their understanding of the material. The study aimed to develop Flipbook learning media and examine its validity, practicality, and effectiveness for fourth-grade students at SD Negeri 040544 Dolat Rayat. The research used the Research and Development method with the ADDIE model, covering analysis, design, development, implementation, and evaluation. The subjects were material experts, media experts, teachers, and fourth-grade students. Data were collected through interviews, questionnaires, and learning achievement tests, and were analyzed descriptively using percentages and N-Gain analysis. The results showed that the Flipbook media was highly valid, with scores of 97.5% from material experts and 95% from media experts. It was also highly practical, with teacher and student response rates of 92.9% and 85.46%, respectively. In terms of effectiveness, the N-Gain results were 15.63% high, 65.63% medium, and 18.75% low. Therefore, the Flipbook media was considered valid, practical, and effective for Pancasila Education in elementary school.